Pengaruh Pemberian POC (Lamtoro, Batang Pisang, Sabut Kelapa) Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Ahmad Fauzan; Yulfi Desi; Syamsuwirman (Jurnal Research Ilmu Pertanian, 2022)
Research on the effect of giving POC (lamtoro, banana stems, and coconut fiber) has been carried out in Korong Gadang Village, Kuranji District, Padang City, West Sumatra. The study was conducted from April to August 2021. The aim of the study was to obtain the best dose of POC (lamtoro, banana stem, and coconut fiber) for the growth of cacao seedlings (Theobroma cacao L.). The study used a completely randomized design (CRD) with 5 treatments and 5 replications, so there were 25 experimental units. Each experimental unit consisted of 4 seedlings and all seedlings were observed. As treatment, several doses of POC (lamtoro, banana stem, and coconut fiber) were used, namely: A = Without POC, B = POC 100 ml/polybag, C = POC 200 ml/polybag, D = POC 300 ml/polybag, and E = POC 400 ml/polybag. The results showed that the effect was not significantly different on the increase in the number of leaves, the longest leaf length, the widest leaf width, stem diameter, taproot length, wet weight of cocoa seeds, and dry weight of cocoa seeds, while the increase in seed height showed a significantly different effect. The best dose of POC has not been obtained for the growth and development of cocoa seedlings. From the results of the research that has been done, it is recommended to carry out further research with a larger dose difference